Problematika Bentuk Bumi: Kajian Komparatif Historis Sains Serta Perspektif Al-Qur’an Dan Sunnah - Salam, Hisbullah; Alamsyah, Alamsyah (Universitas Islam Negeri Mataram, 2022)
This article discusses the problems of the shape of the earth: a comparative historical study of science and the perspective of the Qur'an and Sunnah. Among the scientific studies that are quite warm and test the existence of modern science in recent years is the debate between adherents of the spherical Earth theory (spherical and ellipsoid) and adherents of the flat Earth theory (flat earth). This issue becomes a very serious problem because each party not only shows scientific evidence, but also uses the arguments of the Qur'an and hadith to strengthen their arguments. From a scientific point of view, flat-Earthers argue against the spherical Earth theory such as the invisible curvature of the Earth based on Samuel Rowbotham's experiments, claims that NASA fabricated photos of the Earth and satellites are mere lies, there is no gravity, the north pole is the center of the Earth and so on. Other Meanwhile, in terms of syar’i texts, the commentators also differ in opinion about how the Earth actually looks like. What was put forward by adherents of flat earth was then responded by adherents of round Earth with a number of scientific arguments. In this paper, the authors present a comparison between the flat earth theory and rebuttals from adherents of the spherical earth theory in several approaches, such as the development of history, science, the study of astronomy and interpretation of the Qur'an.